Brain Structural Changes in Carpal Tunnel Syndrome Patients: From the Perspectives of Structural Connectivity and Structural Covariance Network. Issue 6 (11th October 2021) - Li, Yu-Lin; Wu, Jia-Jia; Ma, Jie; Li, Si-Si; Xue, Xin; Wei, Dong; Shan, Chun-Lei; Zheng, Mou-Xiong; Hua, Xu-Yun; Xu, Jian-Guang
Abstract: BACKGROUND: Carpal tunnel syndrome (CTS) is a common peripheral entrapment neuropathy. However, CTS-related changes of brain structural covariance and structural covariance networks (SCNs) patterns have not been clearly studied. OBJECTIVE: To explore CTS-related brain changes from perspectives of structural connectivity and SCNs. METHODS: Brain structural magnetic resonance images were acquired from 27 CTS patients and 19 healthy controls (HCs). Structural covariance and SCNs were constructed based on gray matter volume. The global network properties including clustering coefficient ( Cp ), characteristic path length ( Lp ), small-worldness index, global efficiency ( Eglob ), and local efficiency ( Eloc ) and regional network properties including degree, betweenness centrality ( BC ), and Eloc of a given node were calculated with graph theoretical analysis. RESULTS: Compared with HCs, the strength of structural connectivity between the dorsal anterior insula and medial prefrontal thalamus decreased ( P < .001) in CTS patients. There was no intergroup difference of area under the curve for Cp, Lp ¸ Eglob, and Eloc (all P > .05). The real-world SCN of CTS patients showed a small-world topology ranging from 2% to 32%. CTS patients showed lower nodal degrees of the dorsal anterior insula and medial prefrontal thalamus, and higher Eloc of a given node and BC in the lateral occipital cortex ( P < .001) and the dorsolateral middle temporal gyrus ( P < .001) than HCs, respectively. CONCLUSION: CTS had a profound impact on brain structures from perspectives of structural connectivity and SCNs.